Devonian F-rich peraluminous A-type magmatism in the proto-Andean foreland (Sierras Pampeanas, Argentina): geochemical constraints and petrogenesis from the western-central region of the Achala batholith - Dahlquist, Juan Andres (2014)
A new LA-ICP-MS crystallization age of 370 ± 8 Ma is presented for monzogranite from the Achala batholith, the largest Devonian igneous body in the Sierras Pampeanas, confirming previous U-Pb zircon ages and indicating emplacement within a relatively short episode. Granitic rocks from the central area of the batholith display restricted high SiO2 contents (69.8–74.5 wt.%). Major element plots show ferroan and alkaline-calcic to calc-alkaline compositions with an A-type signature. High concentrations of the high field-strength elements such as Y, Nb, Ga, Ta, U, Th, and flat REE patterns with significant negative Eu anomalies, are also typical of A-type granites. The aluminium saturation index (1.10–1.37) indicates aluminous parent magmas which are further characterised by high FeO/MgO ratios (2.6–3.3) and F contents of igneous biotites (0.9–1.5 wt%), as well as relatively high AlIV (2.39–2.58 a.p.f.u.) in biotites and the occurrence of primary muscovite. Petrogenetic modelling supports a source enriched in plagioclase and progressive fractional crystallization of feldspar. The central area of the batholith displays small-scale bodies composed predominantly of biotite (80 %), muscovite (10 %) and apatite (10 %), yielding rock compositions with 2.3–5.4 wt. % P2O5, and 6–7 wt.% F, together with anomalous contents of U (88–1,866 ppm), Zr (1081–2,581 ppm), Nb (257–1,395 ppm) and ΣREE (1,443–4,492 ppm). Previous studies rule out an origin of these bodies as metasedimentary xenoliths and they have been interpreted as cumulates from the granitic magma. An alternative flow segregation process is discussed here.